Determination of Antifungal Effects of Some Berry Fruits Ethanol Extracts by Disc Diffusion Method - Oktay Tomar; Gökhan Akarca; Elif Başpınar (Turkish Journal of Agriculture: Food Science and Technology)
There are many natural growth area in Turkey and utilizability is increasingly in different areas. Berry fruits involve several species such as grape (Vitis spp.), currant (Ribes spp.), rosehip (Rosa spp.), strawberry (Fragaria spp.), raspberry (Rubus spp.), pomegranate (Punica spp.), blackberry (Rubus spp.), bilberry (Vaccinium spp.), mulberry (Morus spp.) and cornelian cherry (Cornus spp.). Berries are soft fruits that turn from red to blue or black. They contain a good source of vitamins and minerals, and they have various phytochemical compositions that relevant to consumer health. Different varieties of berries contain quite variable concentrations of ascorbic acid, folic acid, anthocyanin, flavonol, ellagitannins and many diversity of hydroxybenzoic acid. Berries have antioxidant, antimicrobial, antifungal and anticarcinogenic properties due to rich content of phytochemical. In this study, Antifungal effect of ethanol extracts obtained from strawberry, raspberry, pomegranate, blackberry, bilberry, mulberry and cornelian cherry against 7 different subspecies of Penicillium, 6 different subspecies of Aspergillus and Mucor racemosus, Botrytis cinerea, Geotrichum candidum, Cladosporium claudosporioides, Rhizopus nigricans species were determined by using disk diffusion method. As a result of the research; It was determined that 9 different samples had antifungal effect on 18 different mold species at various rate. The highest antifungal effect was observed with 24.65 milimeter zone diameter against Mucor racemosus in pomegranate peel extract. This value was followed by blackberry extract against Penicillium glaucum and Penicillium chrysogenum with 20.54 and 20.03 milimeter zone diameter, respectively. It was concluded that the lowest antifungal effect on mold species apart from Aspergillus flavus in blue bilberry extract.